2023
DOI: 10.1007/s11082-022-04417-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of photocatalytic activity (under visible light) of ultrathin CZTS films produced in different thicknesses by PLD method

Abstract: Cu 2 ZnSnS 4 material has been produced by Pulsed Laser Deposition (PLD) on Soda Lime Glass (SLG) substrates as a function of the number of laser pulses. As the deposition of ablated material has been augmented with increasing number of laser pulses, it has been observed that CZTS-ultrathin lm's thicknesses and particle sizes have been increased, their crystalline structures have been improved.Larger particles limit the transmission of light and cause thin lms to absorb more photons. Therefore, band gaps of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…In this context, CZTS thin films offer an intriguing avenue for exploration, leveraging their unique properties to address these challenges. 4,5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, CZTS thin films offer an intriguing avenue for exploration, leveraging their unique properties to address these challenges. 4,5…”
Section: Introductionmentioning
confidence: 99%
“…In this context, CZTS thin films offer an intriguing avenue for exploration, leveraging their unique properties to address these challenges. 4,5 Light trapping methods increase the absorbency of thin films produced at very low thicknesses. Among these methods, plasmonic nanoparticles (NPs) can be composed of Au, Cu, and Ag metals.…”
Section: Introductionmentioning
confidence: 99%
“…This optimized configuration significantly reduced defect-assisted recombination, thereby improving charge transfer and separation efficiencies. Notably, the half-cell solar hydrogen production efficiency of the optimized CZTSSe photocathode reached 6.47% [ 26 , 27 ]. These accomplishments underscore the promising potential of modified CZTS materials for efficient solar hydrogen production, highlighting the significant role CZTS-based materials could play in enhancing photocathode performance for solar-powered hydrogen generation.…”
Section: Introductionmentioning
confidence: 99%
“…It is clearly found that the CZTS-8-8-8, CZTS-8-6-6, and CZTS-8-6-4 samples display higher absorption in the visible light range (approximately 400−1100 nm) compared to the pure CZTS sample. This result could be attributed to the CZTS samples with larger crystallite size and denser film introduced by the incorporation of the GCD-layer, resulting in better coverage and lower light transmittance, 34,35 It is noted that the bandgap of the sample decreases with the introduction of the GCD-layer. To explain this phenomenon, we classified the CZTS, CZTS-8-8-8, CZTS-8-6-6, and CZTS-8-6-4 samples successively as (B-G)-type mixtures, (A-B)-type mixtures, (A-B)-type mixtures, and (A-B)-type mixtures (Figure S13), based on the results in Table S1 and the categorization method for nonstoichiometric kesterite-type materials.…”
mentioning
confidence: 99%
“…It is clearly found that the CZTS-8-8-8, CZTS-8-6-6, and CZTS-8-6-4 samples display higher absorption in the visible light range (approximately 400–1100 nm) compared to the pure CZTS sample. This result could be attributed to the CZTS samples with larger crystallite size and denser film introduced by the incorporation of the GCD-layer, resulting in better coverage and lower light transmittance, , thereby leading to the prepared films having higher absorption. Notably, among all samples, CZTS-8-6-6 exhibits the strongest visible light absorption, while the CdS buffer layer shows extremely low light absorption.…”
mentioning
confidence: 99%